Lumbar Canal Stenosis Caused by Marked Bone Overgrowth after Decompression Surgery - Hiroya Shimauchi-Ohtaki; Manabu Minami; Toshiyuki Takahashi; Ryo Kanematsu; Fumiaki Honda; Junya Hanakita (Case Reports in Orthopedics)
Narrowing of the lumbar canal due to bone regrowth after lumbar decompression surgery generally occurs at the facet joint; it is exceedingly rare for this phenomenon to occur at the laminar arch. Herein, we describe a case of restenosis caused by marked bone overgrowth at the facet joints and laminar arch after lumbar decompression surgery. A 64-year-old man underwent partial hemilaminectomy for lumbar canal stenosis at the L3/L4 level 12 years ago. His symptoms recurred 7 years after the first surgery. Overgrowth of the laminar arch and facet joints was observed at the decompression site. Thus, partial laminectomy of L3 and L4 was performed as a second surgery. Four years after the second surgery, a laminectomy of L3-L4 was performed for bone restenosis and disc herniation. The underlying mechanism of the remarkable overgrowth of the removed lamina remains unclear. Endochondral ossification signals and mechanosignals should be comprehensively examined.